Routledge handbook of Latin American politics - Kingstone, Peter R., 1964-; Yashar, Deborah J., 1963- (Routledge handbooks., 2012)
Latin America has been one of the critical areas in the study of comparative politics. The region's experiments with installing and deepening democracy and promoting alternative modes of economic development have generated intriguing and enduring empirical puzzles. In turn, Latin America's challenges continue to spawn original and vital work on central questions in comparative politics: about the origins of democracy; about the relationship between state and society; about the nature of citizenship; about the balance between state and market.